The Washington manual of surgical pathology - Humphrey, Peter A.; Dehner, Louis P., 1940-; Pfeifer, John D. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"The aim of this book is to provide a practical manual that is helpful to pathologists and residents in the daily practice of surgical pathology. The text encompasses all anatomic sites in the human body. Each chapter covers tissue handling, gross examination, gross dissection and diagnosis, processing, slide preparation, microscopic diagnosis, special studies, and diagnostic reporting. The format of the book would be modeled after the Washington Manuals for other specialties (such as Medical Therapeutics, Oncology, and Surgery)"--Provided by publisher.